The place of “Southwestern” Khanty among the Khanty dialects: Testimony of metadata and lexicon - Fejes, László (Eesti ja soome-ugri keeleteaduse ajakiri. Journal of Estonian and Finno-Ugric Linguistics, 2022)
Southwestern Khanty is a dialect documented only in the 2008 PhD dissertation by Olga Vaysman. This paper attempts to place Southwestern Khanty among other Khanty dialects. Metadata available on Southwestern Khanty are presented and interpreted: based on these, it remains obscure where Southwestern Khanty is spoken. Additionally, data on the lexicon of Southwestern Khanty are compared with the data of the largest dialectal and etymological dictionary of Khanty. Comparison shows that Southwestern Khanty, despite its name, is closest to the northernmost dialect, Obdorsk Khanty. Kokkuvõte. László Fejes: “Edelahandi” paiknemine handi murrete hulgas: tõendid metaandmetest ja sõnavarast.Edelahandi murre on dokumenteeritud ainult Olga Vaysmani 2008. aasta doktoritöös. See artikkel püüab asetada edelahandi teiste handi murrete hulka. Esitatakse ja tõlgendatakse edelahandi murde kohta saadaolevaid metaandmeid, mille põhjal jääb segaseks, kus edelahandi murret kõneldakse. Lisaks võrreldakse edelahandi leksikoni andmeid handi suurima murde- ja etümoloogilise sõnaraamatu andmetega. Võrdlus näitab, et edelahandi murre on erinevalt nimetusest kõige lähemal põhjapoolseimale dialektile, obdorski murdele.